2006
DOI: 10.1007/s11252-006-0008-1
|View full text |Cite
|
Sign up to set email alerts
|

Place-based urban ecology: A century of park planning in Seattle

Abstract: This research responds to calls from within the field of urban ecology to explicitly incorporate humanities-based research in order to achieve robust interdisciplinarity. Our research provides an example of a place-based urban ecological analysis. We use this framework to analyze over a century of park planning and development within the city of Seattle. We identify four eras of park planning that are linked by a comprehensive 100-year park plan. This case study examines how the political, cultural, and econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Research in this field combines urban socio-ecological and historical perspectives to argue that intra-city disparities in the location of quality parks are the outcome of complex interactions between cultural, ecological, and political processes that continuously reshape urban environments and differentially benefit socio-economically advantaged populations at the expense of poor or low-income communities (Brownlow 2006;Dooling et al 2006). The provision of ecologically adequate-and adequately maintained-vegetation is important for equitable outcomes, especially since neglected parks often create "ecologies of fear" that emphasize legacies of race-based social control and criminalization of environments and their occupants (Brownlow 2006).…”
Section: Social Dimensions Of Green Spaces (Parks) In Urban Areasmentioning
confidence: 99%
“…Research in this field combines urban socio-ecological and historical perspectives to argue that intra-city disparities in the location of quality parks are the outcome of complex interactions between cultural, ecological, and political processes that continuously reshape urban environments and differentially benefit socio-economically advantaged populations at the expense of poor or low-income communities (Brownlow 2006;Dooling et al 2006). The provision of ecologically adequate-and adequately maintained-vegetation is important for equitable outcomes, especially since neglected parks often create "ecologies of fear" that emphasize legacies of race-based social control and criminalization of environments and their occupants (Brownlow 2006).…”
Section: Social Dimensions Of Green Spaces (Parks) In Urban Areasmentioning
confidence: 99%
“…Even more recently, there is growing interest regarding the emotional and psychological benefits of nature in close proximity to urban and suburban areas (Kahn, 2002;Miller, 2005;Dooling et al, 2006), and the consequent need for more areas which satisfy these needs in POS. These changes in the meaning of POS in Western Australia, both major and subtle, have occurred without awareness of the recreational designations upon which the 10% allocation was made in 1955.…”
Section: The Bigger Picture: Greening Pos Between 1955 and 2005mentioning
confidence: 99%
“…Some projected issues are currently under global discussion as additions to POS (Ward Thompson, 2002). For example, research in Seattle (Dooling et al, 2006) has revealed a shift from a primarily human-centric management view to a larger ecological agenda in the 1990s. They reported that "park users wanted not only passive and active recreation opportunities, but they also wanted opportunities for observing urban wildlife species and experiencing 'natural' settings, as well as the preservation of contiguous forested and green areas" (Dooling et al, 2006, p. 313).…”
Section: The Bigger Picture: Greening Pos Between 1955 and 2005mentioning
confidence: 99%
“…The visitors willingly choose, in their opinion, quieter areas. Therefore, subjective sounds perception and its correlation with physical measurements is an important part of creating a soundscape in this type of areas [6,10,11]. The above analysis showed inconsistencies in the perception of sounds.…”
Section: Discussionmentioning
confidence: 99%
“…In this type of park, it is very di cult to isolate di erent functions because a park is always an open space where the introduction of arti cial barriers separating individual zones does not seem to be a good solution. There is also a problem of mutual penetration of noise between such zones [11,12]. Sadowski [13] de ned the acoustic shaping of environment as a process based on the formation of such acoustic conditions that would be the most favourable for human health and activities.…”
Section: Introductionmentioning
confidence: 99%